NT-proBNP level as a substitute for myocardial perfusion scan in preoperative cardiovascular risk assessment in noncardiac surgery - Saeede Esmati; Anahita Tavoosi; Saghar Mehrban; Vahideh Laleh Far; Ali Mehrakizadeh; Shayan Shahi; Farnoosh Larti (BMC Anesthesiology, 2023)
Abstract Background Preoperative cardiovascular risk assessment is one of the main principles before noncardiac surgeries. Cardiac stress imaging, such as myocardial perfusion scan (MPS), is a proposed cardiovascular risk evaluation method according to the latest guidelines. Yet, its efficacy, along with the cost-effectiveness of the method, has been questioned in previous studies. Our study aims to evaluate the utility of N-terminal pro-b-type natriuretic peptide (NT-proBNP) level measurement in predicting postoperative cardiovascular complications in candidates who have undergone an MPS before surgery and compare the results. Methods A cohort of 80 patients with a revised cardiac risk index score of one or more who were scheduled for moderate to high-risk noncardiac surgeries and met the criteria to undergo an MPS for risk assessment were included in the study. All of them underwent an MPS one week before surgery. Their preoperative NT-proBNP, troponin levels, and electrocardiograms were obtained one day before surgery and again on day three postoperative. The predictive efficacy of NT-proBNP levels and MPS were compared. Results Seventy-eight patients underwent surgery, three of which exhibited a rise in troponin level, six showed changes on electrocardiogram, and pulmonary edema was detected in one, three days after surgery. There was no mortality in our patients. The sensitivity and specificity of the MPS for predicting postoperative cardiovascular complications were 100% and 66%, respectively. MPS also had a positive predictive value of 20% and a negative predictive value of 100% in our study. A 332.5 pg/ml cut-off value for NT-proBNP level yielded a sensitivity of 100%, specificity of 79.2%, positive predictive value of 40%, and negative predictive value of 100%. Conclusions Our study reveals the incremental specificity and positive predictive value of NT-proBNP level measurement in preoperative cardiovascular risk evaluation compared to MPS. Given the low feasibility, high costs, and disappointing predictive value of MPS, preoperative NT-proBNP level assessment can be substituted. This method can assist anesthesiologists and surgeons with precisely detecting at-risk patients resulting in taking proper measures to reduce the morbidity and mortality of the proposed patients before and during surgeries.